Istihdamu Toriqotil ‘Asho An Natiq Litarqiyatil Mahaarotil Kalam Litalamidi Al Shof Al ‘Asir Bil Madrasah Atsanawiyah An Nida Selomerto Wonosobo - Farida, Ulif; Sunarko, Asep; Irkhamni, Zulfi; Faida, Farah; Assegaf, Umar Said (DAS Institute, 2023)
The type of research is field research (al-bahts al-maidany) where the researcher collects data directly at the location of the study by observation, interviews, documentation and tests. The approach taken by researchers in this study is a quantitative approach using the Experimental method. The population used is X grade Islamic Boarding School of Senior High School An-Nida Wonosobo with a population of 25 students. The researcher analyzes the data using quantitative data analysis methods and the formula used the t-test formula. The results of the study show that: (1) the process of maharoh kalam learning with the application of the talking stick method consists of four stages: the planning stage, the preparation stage, the implementation stage and the evaluation phase. (2) The learning process of maharoh kalam with the application of the talking stick method has advantages such as: test the readiness of students in the lesson, train students to understand the material quickly, encourage students to active learning, students dare to express opinions. While the disadventage is: making heart gymnastics, students who are not ready then can not answer, make students tense, fear students with questions given by the teacher suddenly, (3) Use the talking stick method effectively to improve students' ability to speak the Basic language of Arabic level. This can be seen from the results of data analysis using the t-test formula which shows that the t-count is greater than the existing standard value (t-table) which is 2.10 <11, 19.